ACCESSIBILITY OF FISHERMEN ASSISTANCE MANAGEMENT IN THE KUSUKA PROGRAM IN MALUNDA DISTRICT MAJENE REGENCY - Yusuf Ahmad; Muh Nur Yamin; Zarni Adia Purna (Universitas Negeri Makassar, 2026)
The low accessibility of fisherman assistance in the KUSUKA Program in Malunda District, caused by inadequate socialization, limited ownership of KUSUKA cards, and complex administrative procedures, hinders the equitable distribution of aid and the effectiveness of the program. This study focuses on the distribution, communication, and program implementation constraints that influence the affordability of assistance for fishermen. Using a qualitative descriptive method through interviews, observations, and document analysis, it was found that these factors constitute the primary obstacles in the implementation of the program. This research involved interviews with seven informants from the Fisheries and Marine Affairs Office and fishing groups to understand the accessibility of assistance within the KUSUKA program. Observations were conducted on fishermen’s activities in accessing aid and the distribution process in the field. Additionally, document analysis was carried out on KUSUKA program policies, annual budget reports, and statistical data related to fishermen in Malunda District. Based on Frenton's (2005) accessibility theory, the communication and information dimensions remain the key aspects that need improvement in this program. This research also highlights the importance of direct involvement from local governments and fishermen's organizations in building a more transparent and efficient distribution system, ensuring that the benefits of assistance are more equitably received by fishermen. The main recommendations of this study include increasing socialization efforts, simplifying administrative procedures, and strengthening coordination with fishing groups. Furthermore, utilizing technology